APLIKASI PENGOLAHAN DATA INVENTARIS PERALATAN KERETA API INDONESIA (PERSERO) DIVISI REGIONAL III SUMATERA SELATAN - Heri Gunawan (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
PT. Kereta Api Indonesia (Persero) Regional Division III South Sumatra in the UPT (Technical Service Unit) Dipo Gerbong, currently using the computer as a tool to record inventory data in the form of recording data goods, procurement data of goods, borrow data of good and returns data of goods. But its use is limited to Microsoft Excel applications as typing and reporting applications, there is no special application that can process inventory data goods quickly and accurately. So if the Head of Dipo Gerbong want to get information about inventory data items, have constraints and have difficulty because the data must be checked one by one in the computer which resulted in the process to get the data or the report takes a long time. Judging from the conditions and problems above, the authors want to do research raised with the title